Some Trapezium-Like Inequalities Involving Functions Having Strongly n-Polynomial Preinvexity Property of Higher Order. (13th August 2020) - Awan, Muhammad Uzair; Talib, Sadia; Noor, Muhammad Aslam; Chu, Yu-Ming; Noor, Khalida Inayat
Abstract : The main objective of this paper is to introduce a new class of preinvex functions which is called as n -polynomial preinvex functions of a higher order. As applications of this class of functions, we discuss several new variants of trapezium-like inequalities. In order to obtain the main results of the paper, we use the concepts and techniques of k -fractional calculus. We also discuss some special cases of the obtained results which show that the main results of the paper are quite unifying one.